Dynamic Brittle Instability Characteristics of 2000 m Deep Sandstone Influenced by Mineral Composition - XianJie Hao; Zeyu Chen; Yingnan Wei; Zhuowen Sun; Qian Zhang; Duoxiang Jin (Shock and Vibration)
The study of dynamic brittleness and failure characteristics is of guiding significance for promoting the full exploitation and utilization of deep sandstone reservoirs. At present, there have been more comprehensive studies on the mechanical properties of deep sandstone reservoirs, but the study of mineral composition on the dynamic brittleness and failure characteristics of deep sandstone reservoirs is relatively weak. In this paper, XRD mineral composition analysis, uniaxial compression experiment, and Brazilian splitting are used to study the influence of mineral composition on mechanical properties and failure characteristics of deep sandstone reservoirs. It was concluded that (1) the mineral compositions of deep sandstone reservoirs are mainly three kinds of oxides: SiO2, Al2O3, and CaO. The failure modes of deep sandstone reservoir samples under uniaxial compression are more complicated, with tension failure and shear failure each accounting for half. In the Brazilian split test, the failure modes of sandstone samples are mainly shear failure. (2) The compressive strength decreases obviously with the increase of CaO content. The contents of SiO2, Al2O3, and CaO all have a great influence on the residual strength of deep sandstone reservoirs. The deformation modulus decreases gradually with the increase of Al2O3 content. (3) The brittleness increases slightly when the content of SiO2 increases, while the brittleness decreases slightly when the content of Al2O3 increases. Considering factors such as strength, modulus, brittleness, and failure characteristics, SiO2 content has the greatest influence on the mechanical properties of deep sandstone reservoirs, followed by Al2O3 content, and CaO content has the least influence. The research results have a guiding role in the utilization and development of oil and gas resources in deep sandstone reservoirs and promote oil and gas development from the middle to deeper layers.